Serum 25-hydroxyvitamin D but not dietary vitamin D intake is associated with hemoglobin in women of reproductive age in rural northern Vietnam - Michalski, Ellen S.; Nguyen, Phuong Hong; Gonzalez-Casanova, Ines; Nguyen, Son; Martorell, Reynaldo; Tangpricha, Vin; Ramakrishnan, Usha (Elsevier, 2017)
Background and objectives Hypovitaminosis D and anemia are both prevalent in Vietnam, and low vitamin D status may be a risk factor for anemia. This study aimed to 1) describe vitamin D intake and its determinants, and 2) examine the associations of vitamin D intake and serum 25(OH)D concentrations with hemoglobin and anemia. Methods and study design We used data from the baseline survey of a pre-conceptual micronutrient supplementation trial in women of reproductive age (WRA) in Thai Nguyen, Vietnam (N = 4961). Vitamin D intake was estimated using a semi-quantitative food frequency questionnaire (FFQ). Multivariable regression models were used for the analyses. Results Median vitamin D intake was 0.2 µg/d (8.0 IU) [IQR: 0.4]. Age, being a farmer, food insecurity, and body mass index (BMI) were inversely associated with vitamin D intake, while socioeconomic status (SES), total energy intake, and education were positively associated with vitamin D intake. Vitamin D intake was not associated with hemoglobin concentration or anemia after adjusting for age, BMI, total energy intake, transferrin receptor, C-reactive protein, α1-acid glycoprotein, SES, occupation, education, ethnicity, and food insecurity (P = 0.56 and P = 0.65 for hemoglobin and anemia, respectively). Controlling for the same covariates, 25(OH)D <50 nmol/L (vs. ≥50 nmol/L) was associated with decreased hemoglobin concentrations (β = −0.91 (SE:0.42), P = 0.03), but not with anemia (P = 0.11). Conclusions Low vitamin D status may be linked to reduced hemoglobin concentrations, but the role of diet in this association was not evident in this population of WRA in Vietnam where dietary vitamin D intake was very low.